Evaluating the Effectiveness of an Instructional Intervention in Knowledge Acquisition about Diet Therapy among Patients with Spinal Cord Injuries - Ali A. Shalash; Ayad M. Mousa (مجلة كلية الطب)
Background: Patients with spinal cord injuries often face unique challenges related to their dietary regimen. Adequate knowledge about dietary regimens is crucial for their overall health, well-being, and management of specific nutritional needs.